Influence of Parameters on Bead Geometry in Robotic GMAW Of Single-Sided Bevel T Joints with A36 Steel - Abdul Razak, Mohd Faizal; Ahmad Fauzri, Irfan Rahimi; Salleh, Zuraidah; Abdul Hamid, Ahmad Hussein; Ramli, Roslin (International Journal of Integrated Engineering, 2025)
This study analyses the impact of welding parameters on the quality of bevel-prepared T-joint welds. The experiments utilised a robotic welding system to ensure consistency and accuracy in the welding procedure. The welding parameters included voltage (20V-22V), current (105A and 110A), and weaving width (0.1mm - 0.3mm), while the travel speed was maintained at 2mm/s within predetermined ranges. The quality of the welds was assessed using Vickers Hardness Testing, which offers insights into the mechanical properties and microstructure of the weld zone. The findings indicate a correlation between the welding parameters and the hardness distribution across the weld bead, heat-affected zone (HAZ), and base metal. The findings indicate a significant relationship between the welding parameters and the hardness distribution throughout the weld bead, heat-affected zone (HAZ), and base metal. Variations in voltage and current have been found to impact the heat input, thereby influencing the cooling rate and, in turn, the microstructure and hardness of the weld. The travel speed significantly influenced weld bead geometry and penetration depth, subsequently affecting the overall quality of the weld. This study offers significant insights into enhancing robotic GMAW processes for T-joint welding with bevel preparation. The results can enhance weld quality and efficiency in automated welding applications across multiple industries.